Cost comparison between built-in security components and some physical characteristics of buildings in Nigeria: Case studies of residential, commercial and institutional buildings in Abuja and Minna - Anifowose .O.M, (Penerbit UKM, 2011)
This paper examines the impact of physical characteristics of buildings on the costs of providing security in building projects. The study achieved this by establishing the existence or otherwise of significant differences between total costs of security components in buildings and (i) the nature of the use of the buildings, (ii) the number of floors in the buildings and (iii) the location of the buildings. The paper employs a survey approach, by utilizing a data collection proforma to capture eighteen (18) different variables spread over various elements in building and security components. The results showed that the total costs of built-in security differed significantly amongst the various uses of the building and buildings located in Abuja, as compared to those located in Minna. (P0.05 = 0.041; 0.022); buildings located in Abuja had a relatively lower value (323.91 compared to 964.57 for buildings located in Minna). The study concluded that, the commercial buildings included in the study samples were mainly simple market stall/warehouse buildings that had few openings, and thus lower costs of securing the buildings. The paper recommended that appropriate designs that incorporate built-in security components should always be the focus/priority of the building owners.